The Precipitation Chemistry And Performance Of The Akita Hematite Process An Integrated Laboratory And Industrial Scale Study - Terry C. Cheng (The Minerals, Metals and Materials Society, 2003)
The Akita Hematite Process is currently the only hydrometallurgical iron removal process producing saleable iron by-products in the zinc industry. In this study, McGill University and Akita Zinc Co. have worked together into elucidating the basic precipitation chemistry of the process from the standpoints of hematite product quality and prevailing precipitation kinetics. This work determined that hematite is produced under the applied conditions (T = 195?200oC,PO2 = 103?414 kPa) directly without prior formation of basic ferric sulphate and transformation of the latter to hematite as thought originally. The rate-limiting step responsible for the long retention time (~180 min) was found to be either the re-dissolution of ferrous sulphate according to the batch reactor studies, or the slow hydrolysis of the remaining ferric sulphate according to the continuous reactor studies. Another interesting contrast between the batch and continuous reactor data was the degree of sulphur contamination (1.5 vs. 3.8%, respectively) and the specific surface area of the product (10 vs. 30 m2/g, respectively). These differences in addition to the co-precipitation of SO4-containing phases such as jarosites, alunite, and anhydrite were attributed to the significantly higher supersaturation level prevailing in the industrial continuous autoclaves that yields highly aggregated sub-micron hematite crystallites contaminated with chemisorbed sulphate ions.